2018
DOI: 10.1002/elsc.201800064
|View full text |Cite
|
Sign up to set email alerts
|

Fish farm effluents are suitable growth media for Nannochloropsis gaditana, a polyunsaturated fatty acid producing microalga

Abstract: Fish farm effluents may be used as culture media for marine microalgae, the cell mass of which constitute an excellent fish feed rich in bioactive compounds. In the current investigation different fish farm effluents were tested as culture media for Nannochloropsis strains. Among them, Nannochloropsis gaditana grew well on the effluent released from the sedimentation tank (EST), which is the final step of the wastewater treatment. Mono‐algal but non‐aseptic cultures were conducted in two types of photo‐bioreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 45 publications
0
16
1
1
Order By: Relevance
“…The biomass yields and growth rates of S . platensis observed in this study were higher than those observed in the studies reported by Tsolcha et al [16], Economou et al [36] and Dourou et al [37]. All of these microalgae cultivations were performed under non-aseptic conditions that, despite minimizing the cost of the process, led to lower biomass yields.…”
Section: Resultscontrasting
confidence: 63%
“…The biomass yields and growth rates of S . platensis observed in this study were higher than those observed in the studies reported by Tsolcha et al [16], Economou et al [36] and Dourou et al [37]. All of these microalgae cultivations were performed under non-aseptic conditions that, despite minimizing the cost of the process, led to lower biomass yields.…”
Section: Resultscontrasting
confidence: 63%
“…Nutrients such as nitrogen and phosphorus are the main ones responsible for eutrophication in water bodies nearby fishery production sites [10]; therefore, the removal of those nutrients is a critical step to prevent negative impacts on the local water environments [11,57]. Wastewater was analyzed for the content of nitrates, phosphates, and other parameters required to identify the quality of the water (Table 1).…”
Section: Fishery Wastewatermentioning
confidence: 99%
“…The application of microalgal cultures as a sustainable process for the removal of nutrients has been studied on wastewater from Oreochromis niloticus [3,20,22,[24][25][26]38], Lates calcarifer [8], shrimp culture [29][30][31], Mugil cephalus [10,32], Sparus aurata [10,16], Scophthalmus maximus [39], and even synthetic wastewater [32,36]. According to the results, the percentage of NO 3 removed (>95%) is similar to that reported by most authors; however, the rate of PO 4 was lower than other authors since the wastewater was supplemented with external P.…”
Section: Supplemented Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…To return treated water back to the fish tank, it can be cleaned so it is safe for fish growth and welfare (Mladineo et al, 2010). Moreover, fish farm effluent is a suitable media for cultivating Nannochloropsis gaditana, a marine algae with a high PUFA content (Dourou et al, 2018). Several studies have reported the possibility of feeding aquaculture fish with microalgae (mostly marine) included in the fish feed formulation.…”
Section: Feeding Fish In Space: Integrated Multi-trophic Aquaculturementioning
confidence: 99%